INTERPRETING CHILDREN’S APPRECIATION OF CHILDREN’S LITERATURE IN THE VISUAL LITERACY ERA - Nopita Trihastutie (Linguistics and Literature Students' Journal, 2023)
This current research explores children’s appreciation of children’s literature in the context of the visual literacy era. The ability of early childhood to appreciate visual literature can be viewed as an early childhood creative ability in the context of early childhood visual literacy. This current research aims to examine how early childhood (age 5-6) appreciates children’s literature (children’s stories on screen) and interpret their appreciation. The theoretical framework of this paper is the concepts of children’s literature, appreciation of literature, and visual literacy. This current qualitative research positions children’s appreciation of children’s literature (children’s stories on screen) in a reader-response approach. Two girls aged 5 and 6 who still could not read and write were involved as the participants (visual text readers). In the initial phase, the two readers have been enjoying their favourite story series, My Little Pony, on YouTube Kids every day for more than a year. The data obtained from the question and answer session was documented and interpreted. The findings show that children appreciate visual literature on screen by configuring particular ideas on the basis of the story’s detailed images. The findings show that children can able to explore the life narratives in the stories: the conditions denoting ‘the being’ and ‘the becoming’ and the struggle between good and bad as the situations demonstrate the conflicts and the solutions. The interpretation of children’s appreciation suggests that their appreciation of the visual literature on digital broadcast platforms refers to two major meanings: imagination and philosophy.Keywords: appreciation, children’s literature, visual literacy